Not quite a block party: COVID-19 street reallocation programs in Seattle, WA and Vancouver, BC - Caislin L. Firth; Barbara Baquero; Rachel Berney; Katherine D. Hoerster; Stephen J. Mooney; Meghan Winters (Elsevier, 2021)
The COVID-19 pandemic has exposed mobility inequities within cities. In response, cities are rapidly implementing street reallocation initiatives. These interventions provide space for walking and cycling, however, other mobility needs (e.g., essential workers, deliveries) may be impeded by these reallocation decisions. Informed by mobility justice frameworks, we examined socio-spatial differences in access to street reallocations in Seattle, Washington and Vancouver, British Columbia. In both cities, more interventions occurred in areas where people of color, particularly Black and Indigenous people, lived. In Seattle, more interventions occurred in areas where people with disabilities, on food stamps, and children lived. In Vancouver, more interventions occurred in areas where recent immigrants lived, or where people used public transit or cycled to work. Street reallocations could be opportunities for cities to redress inequities in mobility and access to public spaces. Going forward, it is imperative to monitor how cities use data and welcome communities to redesign these temporary spaces to be corridors for their own mobility.